Clinical and therapeutic characteristics of hospitalized cancer patients in the Najran Region of Saudi Arabia: a cross-sectional study - Abdallah Y Naser; Hamad S Alyami; Mohammad H. Alyami; Ibraheem S. Banihameem; Mohammad Almusabi; Ahlam M. Alqahtani; Mohammed A. Gannas; Hadi S. Alyami; Hadi J. Al Sulayyim; Saeed F. Alkorbi; Hussain M. Alsagoor; Abdullah M. Alyami; Rubiaan S. Almadi; Salem Hussain Alharethi (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2023)
There are limited studies in the Southern region of Saudi Arabia on the characteristics of hospitalised patients with cancer. The aim of this study was to explore the clinical and therapeutic characteristics of hospitalized cancer patients in the Najran Region of Saudi Arabia. A retrospective cross-sectional observational study was conducted using cancer patients’ medical records at the oncology unit in the King Khalid Hospital in Najran situated in the southern region of Saudi Arabia. Hospitalized patients’ records were extracted between 2014 and 2020. Logistic regression analysis was conducted to identify determinants of ICU admission among cancer patients. A total of 1,678 patients were involved in this study. The mean age was 52.5 (SD: 21.1) years. The average duration of stay was 8.7 days (SD: 13.4). The most commonly reported types of cancer were breast cancer, rectum cancer and colon cancer, accounting for 13.6%, 6.9%, and 6.7%, respectively. A total of 13.9% of the study participants required ICU admission. More than half (57.1%) of the patients were complaining of a moderate to severe case upon hospitalization. Older age (52.5 years and above) and the presence of comorbidities were risk factors that significantly increased the risk of ICU admission (P<.001). Patients with diabetes mellitus, hypertension, heart diseases, stroke, and kidney diseases were more likely to require ICU admissions. Patients with liver cancer were more likely to require ICU admission. Healthcare professionals should give extra care and health education for high risk cancer patients including elderly patients and those with other comorbidities to prevent complications and its associated hospitalization.